Polarized Ferroelectric Polymers for High‐Performance Perovskite Solar Cells - Zhang, Cong‐Cong; Wang, Zhao‐Kui; Yuan, Shuai; Wang, Rui; Li, Meng; Jimoh, Musibau Francis; Liao, Liang‐Sheng; Yang, Yang (Advanced materials (Weinheim), 2019)
In hybrid organic–inorganic lead halide perovskite solar cells, the energy loss is strongly associated with nonradiative recombination in the perovskite layer and at the cell interfaces. Here, a simple but effective strategy is developed to improve the cell performance of perovskite solar cells via the combination of internal doping by a ferroelectric polymer and external control by an electric field. A group of polarized ferroelectric (PFE) polymers are doped into the methylammonium lead iodide (MAPbI3) layer and/or inserted between the perovskite and the hole‐transporting layers to enhance the build‐in field (BIF), improve the crystallization of MAPbI3, and regulate the nonradiative recombination in perovskite solar cells. The PFE polymer‐doped MAPbI3 shows an orderly arrangement of MA+ cations, resulting in a preferred growth orientation of polycrystalline perovskite films with reduced trap states. In addition, the BIF is enhanced by the widened depletion region in the device. As an interfacial dipole layer, the PFE polymer plays a critical role in increasing the BIF. This combined effect leads to a substantial reduction in voltage loss of 0.14 V due to the efficient suppression of nonradiative recombination. Consequently, the resulting perovskite solar cells present a power conversion efficiency of 21.38% with a high open‐circuit voltage of 1.14 V. Perovskite solar cells based on polarized ferroelectric polymers are fabricated by doping the ferroelectric polymer into the perovskite layer with different polarizing electric fields and different doping concentrations, different polarized ferroelectric polymers' interlayers between the perovskite and the hole‐transporting layer, and both doping and interlayer. After these treatments, the fabricated devices show a maximum power conversion efficiency of 21.38%.